SELECTION OF DNA MATRIX FOR JUSTIFICATION OF THRESHOLD FOR CONTAMINATION OF PROCESSED MEAT PRODUCTS WITH UNDECLARED POULTRY COMPONENTS - M. Yu. Minaev; G. I. Solodovnikova; K. A. Kurbakov (Теория и практика переработки мяса, 2017)
Diﬀerentiation between adulteration and accidental meat raw material contamination in meat industry enterprises that carry out the combined processing of slaughtering products from farm animals and poultry is necessary to establish a threshold of technically non-removable impurities. Justiﬁcation of the thresholds, e.g. for chicken meat, requires determination of the target analytical matrix, which content in meat raw material is stable. In the Russian certiﬁed methods, the species-speciﬁc DNA matrix for chickens is a multi-copy gene of cytochrome B in mitochondrial DNA. Taking into consideration that mitochondrial DNA copy number can depend on a muscle ﬁber type, animal age, and other factors, the eﬀectiveness of using multi-copy mitochondrial genes for quantifying the poultry content in meat products was justiﬁed in this study. Analysis of the samples from the pectoral and hip muscles of three chicken carcasses and one duck carcass obtained from diﬀerent manufacturers showed that the poultry pectoral and hip muscles contained approximately equal amounts of mitochondrial DNA, which allows its use as a matrix to justify the level of technically non-removable chicken impurities in ﬁnished meat products.